2022
DOI: 10.1186/s13048-022-00962-w
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key genes associated with polycystic ovary syndrome (PCOS) and ovarian cancer using an integrated bioinformatics analysis

Abstract: Background Accumulating evidence suggests a strong association between polycystic ovary syndrome (PCOS) and ovarian cancer (OC), but the potential molecular mechanism remains unclear. In this study, we identified previously unrecognized genes that are significantly correlated with PCOS and OC via bioinformatics. Materials and methods Multiple bioinformatic analyses, such as differential expression analysis, univariate Cox analysis, functional and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 62 publications
0
23
0
Order By: Relevance
“…However, in recent years, large-scale sequence analysis has reported various genetic abnormalities in prostate cancer, other than AR. Molecular pathways brought about by these mutations are related to malignancy and drug resistance in prostate cancer [30]. Our study suggests that AR and OGN expression may be prognostic predictors of mHSPC.…”
Section: Discussionmentioning
confidence: 65%
“…However, in recent years, large-scale sequence analysis has reported various genetic abnormalities in prostate cancer, other than AR. Molecular pathways brought about by these mutations are related to malignancy and drug resistance in prostate cancer [30]. Our study suggests that AR and OGN expression may be prognostic predictors of mHSPC.…”
Section: Discussionmentioning
confidence: 65%
“…47 both PCOS and ovarian cancer. 49 Consistently, earlier research emphasized the significance of NR4A1 in the differentiation and survival of Ly6C-monocytes, as well as their maturation from myeloid dendritic precursors. 50,51 In addition, NR4A1 depletion triggers proinflammatory M1 macrophage polarization with heightened TLR signaling.…”
Section: Discussionmentioning
confidence: 70%
“…In this study, they confirmed that OGN expression in OC patients was positively correlated with the expression of several m 6 A regulators. We speculate that m 6 A can regulate the occurrence of OC and PCOS through a certain signalling pathway through OGN and even participate in the malignant transformation of PCOS [111].…”
Section: Polycystic Ovarian Syndrome (Pcos)mentioning
confidence: 93%